Just Cake Cake House/ Nurul ‘Ain Abu Bakar… [et.al.] - Abu Bakar, Nurul ‘Ain; Mering, Valarie Aren; Net, Viviennie Emie; Indang, Sylvia Nu; Umar, Norasikin; Rufus, Keelly (2009)
Just Cake Cake House is a partnership business which ventures and major in the production of traditional cakes and modern cakes as well as providing consultant service and cafe for our customers. The business consists of five shareholders and all shareholders had agreed as stated in agreement letter which the amount of capital, profit and loss will be divided as stated ratio. We had chosen this kind of business because it shows the equality and no one will be discriminated as the profits and losses are equally divided in the end of the accounting period. In other way, the partnership is a perfect option to be taken because the shareholders will always sharing ideas and knowledge in order to gain profit and achieve high productivity time to time.